Planning and designing of digital archival information systems - Rajh, Arian (Array, 2009)
Digital archival information systems can be planned and designed by following the most prominent records management methodologies like ISO 15489, related standards and DIRKS, or by following project management approach. Project management approach means planning and designing of digital archival information system as a cost and time-bound project and performing monitoring and evaluation activities in these perimeters. This approach can be done by following different project management methodologies like PRINCE2 or Project Cycle Management. The aim of this article is to explain these available options, to compare them and to make recommendations based on assessment of capabilities of an organisation in which the potential digital archival information system is to be planned and designed. Project cycle management is suitable methodology for organisations in which digital archive developers do not have sufficient administrative capabilities or enough staff with technical know-how to develop digital archive without outsourced technical assistance, but are allowed to apply for European financial aid, such as IPA or other funds in the future.